2011
DOI: 10.1128/jb.01415-10
|View full text |Cite
|
Sign up to set email alerts
|

The ColR/ColS Two-Component System Plays Multiple Roles in the Pathogenicity of the Citrus Canker Pathogen Xanthomonas citri subsp. citri

Abstract: Bacterial citrus canker disease, which is caused by Xanthomonas citri subsp. citri, is one of the most devastating diseases of citrus plants. In this study, we characterized the role of the two-component regulatory system ColR/ColS in the pathogenicity of X. citri subsp. citri. colS mutants (256A10 and 421E7), colR mutants (386C6 and 417E10), and a colR colS double mutant (306DSR) all lost pathogenicity and produced no symptoms on grapefruit leaves inoculated by either pressure infiltration or the spray method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 47 publications
(56 reference statements)
3
71
0
3
Order By: Relevance
“…This view has been further verified by the isolation of a set of 7 genes, colR , fhaB , fliC , galU , gumD , wxacO and rbfC , which were previously characterized to be important for Xac biofilm formation [10], [11], [15], [18], [19], [20]. Thus, our procedure will mostly likely validate the 33 novel biofilm-related genes identified in this study.…”
Section: Discussionsupporting
confidence: 66%
“…This view has been further verified by the isolation of a set of 7 genes, colR , fhaB , fliC , galU , gumD , wxacO and rbfC , which were previously characterized to be important for Xac biofilm formation [10], [11], [15], [18], [19], [20]. Thus, our procedure will mostly likely validate the 33 novel biofilm-related genes identified in this study.…”
Section: Discussionsupporting
confidence: 66%
“…On: Thu, 04 Apr 2019 13:22:49 glucan biosynthesis (Malamud et al, 2012), a twocomponent signal transduction system encoded by colS/ colR (Yan & Wang, 2011) and a LOV protein (Kraiselburd et al, 2012) are the elements found to be a requirement for Xcc biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…citri . These include the ColS/ColR two-component system (TCS) [21], filamentous-like adhesin [13], flagellin [15], UTP-glucose-1-phosphate uridylyltransferase [22], xanthan [5], [14], LPS synthesized by wxacO and rbfC [23], the photosensory protein Lov (light, oxygen, voltage) [24], the haloacid dehalogenase-like phosphatase XAC0482, and the two-component sensor RbfS [25]. Of the identified genes associated with biofilm formation, several were also thought to be involved in pathogenesis.…”
Section: Introductionmentioning
confidence: 99%